2018
DOI: 10.20960/nh.1919
|View full text |Cite
|
Sign up to set email alerts
|

Studying food security among students: a comparative case study between public and private universities in Quito-Ecuador

Abstract: ResumenIntroducción: la nutrición parenteral (NP) en la infancia es un tratamiento cuyas características son muy variables en función de la edad y la patología que presente el paciente. Material y métodos: el grupo de Estandarización y Protocolos de la Sociedad Española de Nutrición Parenteral y Enteral (SENPE) es un grupo interdisciplinar formado por miembros de la SENPE, Sociedad Española de Gastroenterología, Hepatología y Nutrición Pediátrica (SEGHNP) y Sociedad Española de Farmacia Hospitalaria (SEFH) que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
1
1
Order By: Relevance
“…Pupils' Level of Understanding of Food Security through the Sustainable Gardens Programme The findings showed that primary school pupils have high understanding of the importance of nutritious food and a balanced menu in maintaining their health. These findings contradict the findings presented in Eche & Herrera (2018) which showed that private university students have lower knowledge of food safety than public university students despite having better food access. In addition, the interview results presented in Law et al (2015) study showed that students have known understanding and could not explain the term food security accurately.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Pupils' Level of Understanding of Food Security through the Sustainable Gardens Programme The findings showed that primary school pupils have high understanding of the importance of nutritious food and a balanced menu in maintaining their health. These findings contradict the findings presented in Eche & Herrera (2018) which showed that private university students have lower knowledge of food safety than public university students despite having better food access. In addition, the interview results presented in Law et al (2015) study showed that students have known understanding and could not explain the term food security accurately.…”
Section: Discussioncontrasting
confidence: 99%
“…A study by Eche & Herrera (2018) involved 730 students from a private university, the University of The Americas and a public university, University of Ecuador (public), Quito, Ecuador. The findings of this study show wide socioeconomic differences between households among students in both institutions; nearly 50% of respondents faced the threat of food security due to factors such as economic restrictions, limited household food spending and high food prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the one hand, food security implies the availability of adequate supplies at the global and national levels. On the other hand, the problem is in the adequate and balanced nutrition and well-being (Eche, Hernández-Herrera, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Las medidas empleadas para controlar y evitar la propagación del virus han representado un importante impacto en la economía, lo cual, ha repercutido negativamente en muchos hogares. El aumento en los precios de los alimentos, el gasto en alimentos de los hogares y las restricciones económicas han sido reconocidos como factores causales de hasta el 50% de la inseguridad alimentaria en hogares de estudiantes universitarios (Eche, et al, 2018).…”
Section: Introductionunclassified